The assessment of caregiver self-efficacy in a virtual eating disorder setting - Nickolas M. Jones; Jessica H. Baker; Bek Urban; David Freestone; Angela Celio Doyle; Cara Bohon; Dori M. Steinberg (Journal of Eating Disorders, 2023)
Abstract Background Caregiver self-efficacy is thought to be a key component for successful family-based treatment (FBT) for individuals with eating disorders. As such, interventions aimed at enhancing caregiver self-efficacy, often measured via the Parents Versus Anorexia scale, have been a focal point of FBT literature. However, studies looking at the relationship between caregiver self-efficacy and treatment outcomes have been mixed. We aimed to better understand the influence of caregiver self-efficacy on eating disorder treatment outcomes during FBT. Methods Caregiver self-efficacy was measured using the Parents Versus Eating Disorders (PVED) scale, an adapted version of the Parents Versus Anorexia scale, in a sample of 1051 patients with an eating disorder and 1528 caregivers (patients can have more than one caregiver) receiving virtual FBT. Across two multilevel models, we tested how caregiver self-efficacy changed over time and its association with changes in eating disorder symptoms and weight over the first 16 weeks of treatment. Results Over treatment, PVED scores increased (b = 0.79, SE = 0.04, CI [0.72, 0.86]) and starting PVED scores were predictive of improved eating disorder symptoms (b = − 0.73, SE = 0.22, CI [− 1.15, − 0.30]), but not weight (b = − 0.96, SE = 0.59, CI [− 2.10, 0.19]). We also found that PVED change-from-baseline scores were predictive of weight (b = − 0.48, SE = 0.03, CI [− 0.53, − 0.43]) such that patient weight was lower when caregiver reports of PVED were higher. Likewise, the association between caregiver change in PVED scores and weight varied as a function of treatment time (b = 0.27, SE = 0.01, CI [0.24, 0.29]). Results were consistent when isolating patients with anorexia nervosa. Conclusions Caregiver self-efficacy during FBT improved over time but was not robustly associated with treatment outcomes. This may, in part, be due to psychometric properties of the PVED scale. We describe these issues and illustrate the need for development of a new measure of self-efficacy for caregivers supporting their loved ones through eating disorder treatment.